A Test of the Consumer Jury Method of Ranking Advertisements (Book). - Gault, E. H. (The Accounting Review, 1935)
Reviews the book "A Test of the Consumer Jury Method of Ranking Advertisements," by Neil H. Borden and Osgood S. Lovekin.